The Effect Of Compensation And Leadership On Employee Satisfaction In PT. Rotella Persada Mandiri 1 Perbaungan - Krisna Ari Agrifa Tarigan (Junal Ilmu Manajemen, 2018)
Job Satisfaction Employees in a company are influenced by many factors, including compensation and leadership in the company. Employees who get compensation in accordance with their achievements and performance will feel satisfied with the company and will motivate themselves to improve their performance, as well as leadership. A good leader who is willing to give an opportunity to employees to actively participate in giving their opinions and ideas to advance the company will give satisfaction to employees and make the employee realize that every employee has an important role to increase company success. The purpose of this study was to determine the effect of compensation and leadership on employee job satisfaction at PT. Rotella Persada Mandiri 1 Perbaungan. The population in this study there are employees of PT. Rotella Persada Mandiri 1 Perbaungan with 55 people. This study uses computer aids for the SPSS program version 23.0. The results of this study indicate that: 1. Partially, the Compensation variable has a significant effect on the Job Satisfaction variable and the Leadership variable does not have a significant effect on the Employee Satisfaction variable at PT. Rotella Persada Mandiri 1 Perbaungan.2. Simultaneously, the compensation and leadership variables significantly influence employee job satisfaction at PT. Rotella Persada Mandiri 1 Perbaungan. This means that the compensation and leadership factors can increase employee job satisfaction at PT. Rotella Persada Mandiri 1 Perbaungan.